(untitled) (Journal of the Management Sciences, 2025)
The study investigated the key factors Influencing blockchain technology in supply chain risk mitigation in developing economies with specific consideration of Nigeria. The study employed a survey methodology approach with a sample size of 81 structured questionnaire, through primary method of data collection among relevant stakeholders in the supply chain operations, experts including logistics managers, sourcing officers, transportation managers, and policymakers. Multiple regression was used as a technique for analyzing data, and SPSS was used as the tool of the analysis. The study’s findings suggest that a supportive regulatory environment demonstrates a vital role in the successful adoption of blockchain technology in supply chains. Developing economies often face challenges related to regulatory uncertainty, which can hinder the adoption of innovative technologies. Governments and regulatory bodies actively promote policies that facilitate the use of blockchain for risk mitigation by providing clear guidelines, incentives, and addressing legal challenges businesses are more inclined to adopt such technologies. Regulatory support also fosters trust among supply chain partners and increases the confidence of stakeholders. The study recommends to foster the adoption of blockchain technology in supply chain risk mitigation, it is essential to improve the technology infrastructure in developing economies. The government and private sector should collaborate to invest in robust digital systems, ensuring reliable internet access and technological tools that support blockchain solutions.